2014
DOI: 10.18632/aging.100668
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage signaling regulates age-dependent proliferative capacity of quiescent inner ear supporting cells

Abstract: Supporting cells (SCs) of the cochlear (auditory) and vestibular (balance) organs hold promise as a platform for therapeutic regeneration of the sensory hair cells. Prior data have shown proliferative restrictions of adult SCs forced to re-enter the cell cycle. By comparing juvenile and adult SCs in explant cultures, we have here studied how proliferative restrictions are linked with DNA damage signaling. Cyclin D1 overexpression, used to stimulate cell cycle re-entry, triggered higher proliferative activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…As also aminoglycoside-induced hair cell death failed to activate SC proliferation in explants from p53 fl / fl ;Pax2-Cre mice, we conclude that p53 loss does not facilitate the capacity of SCs to cell cycle re-entry or transdifferentiation. These findings do not contradict with our previous results showing that p53 is upregulated in the early postnatal SCs forced to re-enter the cell cycle 42 . It is known that unscheduled proliferation and consequent DNA damage trigger p53 upregulation, leading to cell cycle arrest that is often accompanied by apoptosis 43 .…”
Section: Discussionsupporting
confidence: 74%
“…As also aminoglycoside-induced hair cell death failed to activate SC proliferation in explants from p53 fl / fl ;Pax2-Cre mice, we conclude that p53 loss does not facilitate the capacity of SCs to cell cycle re-entry or transdifferentiation. These findings do not contradict with our previous results showing that p53 is upregulated in the early postnatal SCs forced to re-enter the cell cycle 42 . It is known that unscheduled proliferation and consequent DNA damage trigger p53 upregulation, leading to cell cycle arrest that is often accompanied by apoptosis 43 .…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies reported that the utricle’s capacity for SC proliferation and HC regeneration decreases with age 59 60 . In this study, we also found that with increased age the SC proliferation and HC mitotic regeneration induced by Notch inhibition and β-catenin up-regulation were significantly decreased.…”
Section: Discussionmentioning
confidence: 96%
“…If mitophagy cannot catch up with the demand for the clearance of old and damaged mitochondria, high levels of ROS would damage cell molecules including proteins, membrane lipids, and nucleus DNA. [102][103][104] A decline of autophagy thus is responsible for cell aging via insufficient turnover of damaged mitochondria; (e) fusion deficiency between autophagosomes and lysosomes. Autophagic vacuoles are accumulated in the liver with age.…”
Section: Autophagy and Aged Livermentioning
confidence: 99%